Case report: A giant bilateral inguinal hernia requiring artificial mesh and multi-stage surgery in infancy; hernioplasty with silo placement to prevent acute compartment syndrome - Nakagawa, Yoichi; Makita, Satoshi; Uchida, Hiroo; Hinoki, Akinari; Shirota, Chiyoe; Sumida, Wataru; Amano, Hizuru; Okamoto, Masamune; Takimoto, Aitaro; Yasui, Akihiro; Ogata, Seiya; Takada, Shunya; et al. (Frontiers in Pediatrics, 2022)
Hernioplasty for giant inguinal hernias can cause abdominal compartment syndrome (ACS) in adults but rarely does in infants. We encountered a case of a giant bilateral inguinal hernia in infancy complicated by ACS after hernioplasty. Silo placement via a skin incision effectively treated ACS, after which the abdominal wall was safely closed. Hernioplasty performed early in the clinical course can help expand the abdominal cavity and avoid ACS. Thus, hernioplasty should be performed earlier if the hernia size in the flank space gradually increases.